1998
DOI: 10.1002/(sici)1099-0720(199812)12:7<s47::aid-acp598>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in suggestibility: examining the influence of dissociation, absorption, and a history of childhood abuse

Abstract: This study examined how individual differences in dissociation, absorption and a history of abuse are related to memory and suggestibility for the details of a personally experienced, known event. One hundred and thirty college students took part in a staged event and completed the Dissociative Experiences Scale (DES), the Tellegen Absorption Scale (TAS), and questions about each participant's history of childhood abuse. One week after the staged event and initial testing, the students were questioned about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 22 publications
7
54
0
3
Order By: Relevance
“…E jellegzetessége miatt az abszorpciós képesség figyelembevétele különbözô vizsgálatokban számos ellentmondásosnak tûnô eredményt tisztázhat. Ezért a TAS a személyiség-és klinikai pszichológia területén kívül olyan izgalmas határterületeken is alkalmazásra talált, mint például a paranormális jelenségek kutatása (French, Santomauro, Hamilton, Fox & Thalbourne, 2008;Granquist és mtsai, 2005), a hamis emlékek generálásának paradigmája (Eisen & Carlson, 1998) vagy a kriminálpszichológia hatáskörébe tartozó, hírességek iránti megszállott rajongás (Sheridan, Maltby, & Gillet, 2006).…”
Section: Bevezetôunclassified
“…E jellegzetessége miatt az abszorpciós képesség figyelembevétele különbözô vizsgálatokban számos ellentmondásosnak tûnô eredményt tisztázhat. Ezért a TAS a személyiség-és klinikai pszichológia területén kívül olyan izgalmas határterületeken is alkalmazásra talált, mint például a paranormális jelenségek kutatása (French, Santomauro, Hamilton, Fox & Thalbourne, 2008;Granquist és mtsai, 2005), a hamis emlékek generálásának paradigmája (Eisen & Carlson, 1998) vagy a kriminálpszichológia hatáskörébe tartozó, hírességek iránti megszállott rajongás (Sheridan, Maltby, & Gillet, 2006).…”
Section: Bevezetôunclassified
“…Tal conduz-nos a pensar que, muito possivelmente, alguns pais podem não ter assinalado o abuso sexual de que foram alvos, ou então, outros pais, vítimas de abuso sexual durante a infância ou adolescência, optaram por não devolver o questionário, o que pode ser uma limitação do estudo, no que refere particularmente a este tipo de abuso. Esta é mais uma limitação que gostaríamos de assinalar e que tem sido noticiada (Eisen et al, 1998;Epps et al, 1999).…”
Section: Discussão Dos Resultadosunclassified
“…A prevalência de história de abuso físico na infância e adolescência, com base nos relatos na idade adulta, é estimada em 14 a 50% dos sujeitos das amostras recolhidas na comunidade, tendo em conta as amostras e os instrumentos que usam diferentes definições para o abuso (Belt & Abidin, 1996;Browne & Hamilton, 1998;Crouch, Milner, & Caliso, 1995;Eisen & Carlson, 1998; Epps, Carlin, & Ward, 1999;Fish & Scott, 1999;Liem & Boudewyn, 1999;Litty, Kowalski, & Minor, 1996;Milner, Robertson, & Rogers, 1990;Paúl, Milner, & Múgica, 1995;Rosen & Martin, 1996).…”
Section: Introductionunclassified
“…This effect has also been examined in adults (e.g., Eisen & Carlson, 1998;Eisen, Morgan, & Mickes, 2002;Gudjonsson, 1986Gudjonsson, , 1987Gudjonsson, , 1988Gudjonsson, , 1990Gudjonsson, , 1992aRoebers & Schnieder, 2000) and is relevant in understanding coerced confessions obtained during police interrogations (Gudjonsson, 1989(Gudjonsson, , 1992bGudjonsson & Clark, 1986;Gudjonsson, Sigurdsson, & Einarsson, 2004;Kassin, 1997). Gudjonsson and his colleagues have identified several individual difference factors that are related to this general type of suggestibility effect, including but not limited to acquiescence (Gudjonsson, 1990;Gudjonsson & Clark, 1986), short-term memory (Gudjonsson, 1987), assertiveness (Gudjonsson, 1988), locus of control (Gudjonsson & Lister, 1984), and intellectual ability (Gudjonsson, 1990).…”
Section: Immediate Acceptance Of Misinformationmentioning
confidence: 99%
“…Gudjonsson and his colleagues have identified several individual difference factors that are related to this general type of suggestibility effect, including but not limited to acquiescence (Gudjonsson, 1990;Gudjonsson & Clark, 1986), short-term memory (Gudjonsson, 1987), assertiveness (Gudjonsson, 1988), locus of control (Gudjonsson & Lister, 1984), and intellectual ability (Gudjonsson, 1990). Other investigators who have used variations of this approach, have also found relations between errors on misleading questions and dissociation (Eisen & Carlson, 1998;Merckelbach, Muris, Rassin, & Horselenberg, 2000;Wolfradt & Meyer, 1998), fantasy proneness (Merckelbach, Muris, Schmidt, Rassin, & Horselenberg, 1998), age effects (Roebers & Schnieder, 2000), and other individual difference factors (see Eisen, Winograd, & Qin, 2002;Harris et al, 2009;Pipe & Salmon, 2001, for reviews).…”
Section: Immediate Acceptance Of Misinformationmentioning
confidence: 99%